TcMYC2a, a Basic Helix–Loop–Helix Transcription Factor, Transduces JA-Signals and Regulates Taxol Biosynthesis in Taxus chinensis - Zhang, Meng; Jin, Xiaofei; Chen, Ying; Wei, Mi; Liao, Weifang; Zhao, Shengying; Fu, Chunhua; Yu, Longjiang (Frontiers in Plant Science, 2018)
ug. Taxol biosynthesis is significantly regulated by jasmonate acid (JA), one of the most important endogenous hormones in land plants. Nevertheless, the JA-inducing mechanism remains poorly understood. MYC2 is one of the key regulators of JA signal transfer and the biosynthesis of various secondary metabolites. Here, TcMYC2a was identified to contain a basic helix–loop–helix (bHLH)-leucine zipper domain, a bHLH-MYC_N domain, and a BIF/ACT-like domain. TcMYC2a was also found to bind with TcJAZ3 in yeast, which was a homolog of Arabidopsis JASMONATE ZIM-domain JAZ proteins, indicating that TcMYC2a had a similar function to AtMYC2 of JA signal transduction. TcMYC2a was able to affect the expression of GUS reporter gene by binding with the T/G-box, G-box, and E-box, which were the key cis-elements of TASY and TcERF12/15 promoter. TcMYC2a overexpression also led to significantly increased expression of TASY, tat, dbtnbt, t13h, and t5h genes. Additionally, TcERF15, which played the positive role to regulate tasy gene, was up-regulated by TcMYC2a. All these results revealed that TcMYC2a can regulate taxol biosynthesis either directly or via ERF regulators depending on JA signaling transduction.